Self Management Pasien Hipertensi dalam Mengontrol Tekanan Darah - Nurarifah Nurarifah; Risna Damayanti (Jurnal Keperawatan Silampari, 2022)
This study aims to explore the self-management of hypertensive patients during treatment in the Mamboro Public Health Center Work Area. The research method in this study is a qualitative study with a phenomenological approach. The results of the study consisted of six themes, namely diet, physical activity, smoking, antihypertensive medication, blood pressure checks, and social support. Participants have tried to be able to maintain self-management in controlling blood pressure through a healthy lifestyle and adhere to antihypertensive medication but there are some obstacles that caused the participants to not comply with the advice given by health workers such as side effects, long-term treatment. Participants know that Moringa leaves have properties to lower blood pressure but the processing is still not appropriate. In conclusion, increasing understanding to improve self-management of hypertensive patients is appropriate to control blood pressure through the development of self-management improvement modules. Keywords: Hypertension, Self Management, Qualitative Study